A genetic screen for zebrafish mutants with hepatic steatosis identifies a locus required for larval growth. Issue 3 (15th December 2016) - Hugo, Sarah E.; Schlegel, Amnon
Abstract: In a screen for zebrafish larval mutants with excessive liver lipid accumulation (hepatic steatosis), we identified harvest moon ( hmn ). Cytoplasmic lipid droplets, surrounded by multivesicular structures and mitochondria whose cristae appeared swollen, are seen in hmn mutant hepatocytes. Whole body triacylglycerol is increased in hmn mutant larvae. When we attempted to raise mutants, which were morphologically normal at the developmental stage that the screen was conducted, to adulthood, we observed that most hmn mutants do not survive to the juvenile period when raised. An arrest in growth occurs in the late larval period without obvious organ defects. Maternal zygotic mutants have no additional defects, suggesting that the mutation affects a late developmental process. The developmental window between embryogenesis and the metamorphosis remains under‐studied, and hmn mutants might be useful for exploring the molecular and anatomic processes occurring during this transition period.